2013
DOI: 10.1017/s0950268813003014
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus genotypes implicated in two oyster-related illness outbreaks in Ireland

Abstract: We investigated norovirus (NoV) concentrations and genotypes in oyster and faecal samples associated with two separate oyster-related outbreaks of gastroenteritis in Ireland. Quantitative analysis was performed using real-time quantitative reverse transcription polymerase chain reaction and phylogenetic analysis was conducted to establish the NoV genotypes present. For both outbreaks, the NoV concentration in oysters was >1000 genome copies/g digestive tissue and multiple genotypes were identified. In faecal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…It is significant that high concentrations (> 1000 genome copies/g) were detected in oysters sampled from the main harvest area (Site 1) during the high-risk winter months. Similar norovirus RNA concentrations have previously been detected in oysters associated with illness outbreaks (Doré et al 2010 ; Lowther et al 2012a ; Rajko-Nenow et al 2013 ). Based on E. coli monitoring data and despite the high concentrations of norovirus detected, Site 1 was classified as ‘Class A’ harvesting area under EU regulations.…”
Section: Discussionsupporting
confidence: 79%
“…It is significant that high concentrations (> 1000 genome copies/g) were detected in oysters sampled from the main harvest area (Site 1) during the high-risk winter months. Similar norovirus RNA concentrations have previously been detected in oysters associated with illness outbreaks (Doré et al 2010 ; Lowther et al 2012a ; Rajko-Nenow et al 2013 ). Based on E. coli monitoring data and despite the high concentrations of norovirus detected, Site 1 was classified as ‘Class A’ harvesting area under EU regulations.…”
Section: Discussionsupporting
confidence: 79%
“…Oyster‐associated NoV outbreaks often contain multiple genotypes, and comprise total of 2 to 3 log 10 GEC/g of digestive tissues (Alfano‐Sobsey and others ; Lowther and others ; McIntyre and others ; Rajko‐Nenow and others ). The association of RNA quantity with the risks to human health may depend on the methodology employed for the downstream analysis of the viral genome (Lowther and others ).…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenic analysis of the NoV viral genome revealed that the strain belonged to the GII.4 Sydney (Figure ), which has been the dominant NoV outbreak strain in the U.S. from 2013 to 2014 (Vinjé ). Other strains (GI.2, GI.3, GI.4, GII.b, GII.e, GII.2, GII.6, GII.12, and GII.13) have been identified in the shellfish or clinical specimens obtained from shellfish‐associated NoV outbreaks; however, the NoV genotypes identified in oysters could rarely be linked to the outbreak cases (Alfano‐Sobsey and others ; McIntyre and others ; Rajko‐Nenow and others ; Rajko‐Nenow and others ; Verhoef and others ). The nucleotide sequence of the stool NoV GII determined in this study is deposited in GenBank under the accession number KP455650.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, the HPNV displayed 99% sequence homology to a short (300-nt) norovirus VP1 sequence detected in oysters (15). These oysters had been sampled because they were associated with a foodborne gastroenteritis outbreak in Ireland in 2012 (15). Oyster samples were collected from the restaurant where the outbreak occurred and from their harvesting area.…”
Section: Discussionmentioning
confidence: 99%